Slow Fashion, Fast Fashion and Intellectual Property Rights - Vyas, Ragi (Stockholm Intellectual Property Law Review, 2025)
This work explores how intellectual property protection interacts with the realities of the modern fashion industry, especially considering the fast fashion industry. It begins by outlining the sociological mechanisms that shape fashion to illustrate why the protection of fashion might be different from the protection of other works. The piracy paradox, a theory that suggests that copying and imitation within the fashion industry is beneficial for designers, is introduced as a central analytical lens. Following this, the alternative forms of Intellectual Property protection for fashion are presented to examine how well these are aligned with the realities of fashion.